Una nueva fuente de inspiración para la educación científica - López Rupérez, F. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1995)
In this paper, physics, epistemology and the teaching and learning of physics are presented as a transdisciplinary system. With such an approach, the fundamental principles of contemporary physics considered in a qualitative form —epistemological principles— are postulated as a source of inspiration for Science Education. In this way, a new trend for fundamental educational research is defined.